Fostering a Tech Culture through Campus Collaborations: A Case Study of a Hackathon and Library Partnership. Issue 2 (3rd April 2022) - Longmeier, Meris M.; Dotson, Daniel S.; Armstrong, Julia N.
ABSTRACT: Hackathons are time-bound, competitive coding contests that are often judged for prizes. Their name originates from joining hacking, playful exploration of hardware and software issues, with marathons, endurance competitions. The intent is to challenge participants to build working prototypes of hardware or software in a short time period, anywhere from one day to several weeks, though typically between 24–28 hours. While they are a mainstay in computer science fields, they are becoming increasingly popular in other domains, including libraries. Libraries have long championed life-long learning, a democratization of data, and access to information. These are similar mentalities of the maker movement, echoed in hackathons. Rapid iteration, problem solving, and cooperative learning are regularly present at events and within library systems. This paper details a case study of one institution's growth from a hackathon event host to deeper library engagement and partnership with an informal learning program. The authors will highlight benefits that both partners observed and will end with a pitch for why other libraries should consider hosting similar events. Finally, several recommended resources for libraries who are contemplating hosting hackathon events will be presented.